Energy spread tuning of a laser-plasma accelerated electron beam in a magnetic chicane. (29th May 2020) - Roussel, E; André, T; Andriyash, I; Blache, F; Bouvet, F; Corde, S; Oumbarek Espinos, D; Ghaith, A; J-P Goddet; Kitegi, C; Kononenko, O; Labat, M; et al.
Abstract: Laser-plasma accelerators (LPA) deliver relativistic electron beams with high peak current and low emittance, with energies up to the GeV-level in only few centimetres. However, the divergence and the energy spread of these beams remain too large for potential light source applications. A magnetic transfer line can be used to manipulate the electron beam phase-space and select the transmitted energies with a slit located at its center. We will show that with a proper focusing optics along the line, one can tune the energy spread of the beam at a given energy without loss and produce undulator radiation with controlled bandwidth. We present analytic studies, numerical simulations and experimental results on the controled electron beam transport and application to undulator radiation with a control of the bandwidth.